Global Research Patterns In Islamic Finance: A Bibliometric Analysis - Munawaroh, Siti Ikmatul; Rahman, Taufiqur (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This study aims to map the gaps in understanding the direction of development in Islamic finance, trending topics, and areas that require further research. This study is a literature review through bibliometric analysis taken from scientific publication data related to Islamic finance published in the Scopus database from 1990-2024. The analysis includes developing the number of publications by country, institution, author, and the relationship between journals, authors, and research topics. Visualization of bibliometric networks with VOSviewer and Biblioshiny to identify key topic areas. The results show that Malaysia has the most research, with 3558 articles. M. Kabir Hassan is the most influential author. The International Islamic University Malaysia (IIUM) is the affiliate with the most publications, and some keywords have not been widely researched, such as crypto, bitcoin, and others. This study can be used as new academic research based on topics such as blockchain technology, crypto, and bitcoin, subject norms, planned behavior, Islamic microfinance, and Islamic stock. This research can make it easier for academics to understand research trends in Islamic finance so that they can provide innovations in further research.